Factors Affecting Quality of Health Service and Patient Satisfaction in Community Health Centers in North Lampung, Sumatera - Mulia Yuli Widayati; Didik Tamtomo; Rita Benya Adriani (Journal of Health Policy and Management, 2017)
Background: Quality of health service and patient satisfaction are an important element in providing a health service. Assessing and evaluating a health service based on user perceptions are important for continuous improvement of health services. This study aimed to examine the factors affecting the quality of health service and patient satisfaction in community health centers in North Lampung, Sumatera, Indonesia.Subjects and Method: This was an analytic observational study with a cross-sectional design. This study was conducted in 25 community health centers in North Lampung, Sumatera, in January 2017. A total sample of 200 out-patients was selected for this study by simple random sampling and stratified random sampling for community health center. The dependent variables were quality of service and patient satisfaction. The independent variables were education, income, a frequency of visit, and accreditation status of community health center. The contextual effect was measured by accreditation status of community health center. The data were collected by questionnaire and analyzed by linear regression multilevel model.Results: Factors affecting quality of health service were income (b= -1.09, 95% CI= -5.71 to 3.52, p = 0.641), education (b = -11.48, 95% CI= -16.07 to -6.88, p< 0.001), and frequency of visits (b=6.88, 95% CI= 2.53 to 11.23, p=0.002). Intraclass correlation= 6%. Factors affecting patient satisfaction were income (b= -1.07, 95% CI= -1.58 to -0.56, p<0.001), education (b= -0.77, 95% CI= -1.31 to -0.23, p=0.005), frequency of visits (b= 0.88, 95% CI= 0.39 to 1.38, p<0.001), and quality of service (b=0.04, 95% CI= 0.02 to 0.06, p<0.001). Intraclass corelation= 13.79% indicating considerable contextual effect of accreditation status of community health center.Conclusion: Quality of service is affected by income, education, and frequency of visits in community health center. Patient satisfaction is affected by income, education, a frequency of visits, and quality of service. Accreditation status of community health center has a considerable contextual effect on patient satisfaction.Keywords: quality of service, patient satisfaction, accreditation status, community health center, multilevel analysisCorrespondence: Mulia Yuli Widayati. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A Surakarta. Email: muliayuli@yahoo.co.idJournal of Health Policy and Management (2017), 2(2): 165-175https://doi.org/10.26911/thejhpm.2017.02.02.08